Higher Education Finance Reform in the Czech Republic - Matthew S. McMullen (Arizona State University, 2000)
Throughout Europe and especially the former communist countries of Central and Eastern Europe, universities and governments are evaluating ways to finance higher education other than the current dominant model of almost total government support. With government pressure to use limited funds in other areas (e.g., health care, environment, and the like) higher education institutions are being encouraged to become more economically self-sufficient. Some of these reforms have included establishing closer ties with regional businesses and introducing tuition and user fees to offset some of the costs of university operations. The particular focus of this report is on the new methods of financing higher education in the Czech Republic.